Creating innovations for solutions of logistics problems: opportunities, risks, and limitations - A. I. Gorbatov (Вестник университета)
The article provides an assessment of innovation activity state in logistics companies in the second half of 2022 and 2023 as well as the potential consequences of low level of investment in innovation.   The relevance of the article is determined by the objective features of the development of the logistics industry in the Russian Federation, primarily in the context of international import and export trade under the conditions of sanctions restrictions as well as increased competition of logistics companies on the market and competitive pressure from international logistics companies which enter the Russian market.   The purpose of the study is to assess the characteristics of the functioning of the logistics industry and the prospects for its development, which can have a significant impact on the international movement of goods.   An assessment is made of companies’ strategies to maintain their market share, increasе this share through interaction with the labour market as well as tо use additional tools for obtaining and maintaining a market advantage. A conclusion is drawn about the influence of a number of factor criteria on the further development of the industry and those resources associated with investments in innovation that the company’s owners have for the future development of their business.